Endometrial abnormalities on transvaginal ultrasonography and histopathology in women after quinacrine sterilization - Afzal, Saira (Professional Medical Publicaitons, 2014)
Objective: To describe endometrial abnormalities on transvaginal ultrasonography and histopathology in women after quinacrine sterilization. Methods: It was an analytical cross sectional study conducted during February 2012 to April 2013. The sample size calculated at 95% confidence level was 540. Sampling technique used was simple random sampling. The medical history, examination, transvaginal ultrasonography and biopsy of suspected lesion was performed in quinacrine sterilized women. Results: The calculation of statistics showed the mean age at quinacrine sterilization was 38.5 years, standard deviation 6.517, and standard error 0.461. The endometrium was regular and smooth with homogenous images in 86% (n= 466), irregular endometrium with heterogeneous images on transvaginal ultrasound in 9.4% (n =51) and endometrial growth with high level echoes in 4.2% women (n= 23). The histological findings included hyperplasia and well differentiated adenocarcinoma in two patients respectively. Conclusion: The irregular endometrium, adhesions, and growths were found after quinacrine sterilization. The risk of endometrial growth was more after 10 years duration of quinacrine sterilization.